SAT0354 Changes in hip fracture and association with osteoporosis-related fracture prevention service initiatives. (23rd January 2014) - Clunie, G.; Stephenson, S.; Wilson, S.; Belsey, J.
Abstract : Background: Fracture Liaison Services (FLSs) identify patients who may have osteoporosis, at the time of fracture and facilitate osteoporosis treatment to reduce secondary fracture incidence accordingly. One outcome that can indicate success of an FLS is a reduced hip fracture incidence. Hip fractures are the most costly fractures to Healthcare systems given subsequent morbidity and financial cost of associated health and social care. However, hip fractures are preventable. Given about 50% of hip fractures occur in people who have had a previous ("signal") fragility fracture, such patients are potentially identifiable at the time of a "signal" fracture by FLSs and offered osteoporosis treatment to reduce the risk of hip fracture. Objectives: To evaluate the role of a FLS, in the context of other associated local Healthcare initiatives, on hip fracture incidence over a 6y period (2005-10) through comparing the local observed hip fracture incidence with expected National UK fracture incidence. Methods: A FLS was implemented at The Ipswich Hospital in 2003 and since then all patients >50y with fracture have been screened and treated accordingly for osteoporosis. Hip fracture data was collated by FLS staff continuously since 2005. Local osteoporosis drug prescribing statistics (2006-10) were obtained from The UK NHS Business Service Authority. Expected hip fracture incidence was estimated for 2005-10 by applying age-sex specific hip fracture rates derived from UK Hospital Episode Statistics, to the demographic profile of our local population. Rate ratios were calculated for age groups: 55-64, 65-74, 75-84 and 85+, based on observed fracture incidence. SDs and CIs for the rate ratios were estimated using the Poisson function. Results: For all ages, hip fracture rate ratio (Ipswich vs England) was unity or below (range 0.85-1.00) though with no significant trend over time. This was similar across age groups though for some individual year/age group combinations the hip fracture rate was significantly below the expected values, notably for age ranges 55-64y. Considering all 24 data points (data for 4 age ranges over 6y), Ipswich hip fracture rates were less than expected on 17/24 occasions and significantly (95% CIs) on 5 occasions, 3 of which were in the 55-64y age group. In detail: over the 6 years, for the 55-64y old group, fracture rate ratios varied from 0.5-1.1; for the 65-74y old group from 0.8-1.0; for the 75-84y old group from 0.8-1.2 and for the 85y+ group from 0.8-1.1. From 2006-2010, there was an increase in osteoporosis drug prescribing in the associated Healthcare service area by 50% (20, 000 - 30, 000 prescriptions). Conclusions: Hip fracture rates in Ipswich have been consistently lower than expected for England. A greater reduction in hip fractures is seen in the 55-64y old age group compared to older ages. The reduced hip fracture rates may reflect the success of continual FLS activity but results need to be viewed in the context of increased general osteoporosis drug prescribing. There is little reduction, if any, in hip fracture rates in the very elderly - an age group in which admissions to hospitals for falls is continually increasing in The UK. Disclosure of Interest: None Declared